Plans for planar: phase-noise reduction techniques in voltage-controlled oscillators - Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, A. K. M. Zakir (IEEE, USA, 2019)
To ensure spectral purity in modern RF signal sources, microwave oscillators and voltage controlled oscillators (VCOs) must be designed to perform with low phase noise. Despite the growth of monolithic microwave integrated circuits (MMICs), microstrip planar technology is still used for developing low-phase-noise VCOs due to its design simplicity and low manufacturing cost. This article reviews the attributes of low-phase-noise VCOs and some recent techniques applied for phase-noise reduction in microstrip planar technology. The major challenge in designing VCOs in microstrip planar technology lies in improving the quality factor (Q) of resonators. Different methods to improve Q are presented here for techniques incorporated with microstrip lines and substrate integrated waveguides (SIWs). The tradeoff involved with the tuning range (TR) of VCOs is also emphasized to introduce the design selectivity for wideband applications.